TUNISIA'S ONE-TO-ONE INHERITANCE PHENOMENON: THE ROLE OF PUBLIC SPACE BEHIND THE FAILURE OF MASHRÅªâ€™ Aá¸¤KÄ€M TATA'ALLAQU BI AT TASÄ€WIY FÄª AL MÄªRÄ€á¹ - Nizami, Auliya Ghazna; Haidar, Muhammad; Mutmainnah, Hayyun Ulfah (Jurnal Al-Dustur, 2024)
Tunisia is known as a Muslim country with a progressive Islamic family law order. Progressiveness is shown by efforts to change the rules of the male and female inheritance sections. The standard concept of Islamic inheritance in the division of inheritance between men and women is 2:1, in this case Tunisia seeks to change it to be equal between men and women. This research discusses the Inconsistency of Islamic Family Law in Muslim Countries: A One to One Inheritance Study in Tunisia. This research is a normative-empirical legal research that combines the nature of normative law accompanied by empirical data. The findings of this study suggest at least two main findings as answers to the two problem formulations stated at the outset. First, Islamic family law in Tunisia which is manifested in the form of Majallah al Aá¸¥wÄl Asy Syakhá¹£iyyah (MAS) often gets changes along with changes in the political forces in power in the country. One of the major parts of MAS is the provision for inheritance distribution between men and women as stipulated in article 146, which is considered by one political camp to be unfriendly to women's rights. Second, the potential power of public space legislation is widely used to provide changes to certain regulations, in this case regarding the provisions of inheritance rights for men and women. The feminist camp with the help of public voice succeeded in drafting Aá¸¥kÄm Tata'allaqu bi at TasÄwiy fÄ« al MÄ«rÄá¹¡ which is addressed to article 146 of the MAS.